Misallocation and Manufacturing TFP in China and India. - Hsieh, Chang-Tai; Klenow, Peter (Quarterly Journal of Economics, 2009)
Resource misallocation can lower aggregate total factor productivity (TFP). We use microdata on manufacturing establishments to quantify the potential extent of misallocation in China and India versus the United States. We measure sizable gaps in marginal products of labor and capital across plants within narrowly defined industries in China and India compared with the United States. When capital and labor are hypothetically reallocated to equalize marginal products to the extent observed in the United States, we calculate manufacturing TFP gains of 30%-50% in China and 40%-60% in India. Reprinted by permission of the publisher.